Silicon (Si) biochar for the mitigation of arsenic (As) bioaccumulation in spinach (Spinacia oleracean) and improvement in the plant growth. (10th July 2018) - Zama, Eric F.; Reid, Brian J.; Sun, Guo-Xin; Yuan, Hai-Yan; Li, Xiao-Ming; Zhu, Yong-Guan
Abstract: In many parts of the world, growing crops on polluted soils often leads to elevated levels of pollutants in plant tissues. Minimizing the transfer of these pollutants into edible plant tissues while improving plant growth and productivity is a major area of research. In this study, we investigated the efficiency of silicon-modified biochar in reducing the uptake of As(III) in spinach ( Spinacia oleracean ) while simultaneously increasing the plant biomass. Unmodified biochars (uBC) and silicon-modified biochars (SiBC) were prepared from bamboo at 300 and 600 °C and characterized by Scanning Electron Microscopy with Energy Dispersive X-ray (SEM EDX), Fourier Transform Infrared Spectrometry (FTIR), X-ray Photoelectron Spectrometry (XPS), and X-ray Diffraction analysis (XRD). The bioaccumulation of As(III) in the edible part of spinach significantly decreased by 33.8 and 37.7% following the amendment of, respectively, 2% and 5% SiBC in soil. Biochar amendment increased the concentration of As(III) in pore water by 64.4% as a result of increased soil pH from 6.83 ± 0.4 to 8.01 ± 0.1 and dissolved organic carbon (DOC) from 7.02 ± 3.7 to 22.58 ± 3.7 g kg −1 . However, the uptake of As(III) into spinach was prevented by silicon, which was preferentially transported to the plant through the same transport pathway as As(III). Dry biomass yield in spinach also significantly increased by 67.7% and strongly correlated (R 2 = 0.97) with CaCl2 extractable Si in the plant. The results highlighted the effectiveness of SiBC in reducing the toxic effects of As in the environment and overall dietary exposure to the pollutant. The slow release of Si from biochars (<48.42%) compared to soil (87.39%) also suggested that SiBC can be efficient sources of Si fertilization for annual crops which can significantly reduce the increasing demand for Si fertilizers and their sustainable use in the environment. Graphical abstract: Highlights: Biochars (unmodified and silicon modified) were made from bamboo at 300 and 600 °C. Silicon biochar was effective in decreasing As bioaccumulation in spinach by 37.7%. Silicon prevented As uptake by spinach although pore water As increased by 64.4%. Dry biomass in spinach increased by 67.7% correlating positively with the plant Si. Si biochars mitigate As accumulation in crops and release Si slowly for crop growth.